Antihepatitis B Surface Antigen and Hepatitis C Antibodies among Pregnant Women in an Urban Area of Mwanza City, Tanzania - Elieza Chibwe; Vitus Silago; Edwin Kajoro; Muhsin Juma; Emmanuel Mkumbo; Caroline A. Minja; Fridolin Mujuni; Stephen E. Mshana; Mariam M. Mirambo (Hindawi Limited, 2019)
Background. Hepatitis B and hepatitis C viruses (HBV and HCV) are life-threatening infections of public health importance due to their association with cirrhosis and hepatocellular carcinoma. Despite HBV being moderately endemic in many low-income countries, there is no routine HBV vaccination among child bearing aged women making them at risk of transmitting infections to the foetus during pregnancy. This study investigated the seroprevalence of antihepatitis B surface antibodies (anti-HBs) and HCV antibodies among pregnant women in Mwanza city to provide data that can be used in devising preventive strategies. Methods. A cross-sectional hospital-based study involving 339 pregnant women was conducted between June and July 2017. Data were collected using structured data collection tool. Detection of anti-HBs was performed using enzyme immunoassay while qualitative rapid immunochromatographic tests were employed to detect HCV antibodies. Data was analyzed by using STATA version 13. Results. The mean age of the study participants was 25.6±5.8 years. The prevalence of anti-HBs was 85/339 (25.1%, 95% CI: 20.4-29.6) while that of HCV antibodies was 1/333 (0.3%, 95% CI: 0.1-0.4). By univariate logistic regression analysis, increase in age (OR: 1.04, 95% CI: 1.00-1.09, P=0.03), unknown HIV status (OR: 0.3, 95% CI: 0.11-0.79, P=0.035), and multigravidity (OR: 2.12, 95% CI: 1.18-3.8, P=0.038) were significantly associated with anti-HBs seropositivity. Conclusion. A significant proportion of pregnant women have anti-HBs while the seroprevalence of HCV is low among pregnant women in the city of Mwanza. Routine screening of HBV among pregnant women coupled with appropriate management should be emphasized in developing countries. Further studies to determine seroprevalence of HCV are recommended across the country.